Clinical features, molecular characteristics and surgical management of primary penile mucosal melanoma based on the European Association of Urology Penile Cancer Guidelines. Issue 1 (February 2022) - Cakir, Omer Onur; Pozzi, Edoardo; Castiglione, Fabio; Freeman, Alex; Haider, Aiman; Rees, Rowland; Alnajjar, Hussain M.; Bunker, Christopher; Muneer, Asif
Abstract : Penile mucosal melanoma is an aggressive and rare genital malignancy. The aim of the present study was to review the management and outcomes of a homogenous cohort of patients with histologically confirmed penile mucosal melanoma, at a single specialist centre. A retrospective review of an institutional database identified patients with penile mucosal melanoma over a 10-year period. Patient demographics, histopathological characteristics, type of primary surgery, recurrence, presence of metastatic disease and molecular markers were evaluated. The management of the patients was initially based on the European Association of Urology (EAU) penile cancer guidelines which are primarily for squamous cell carcinoma with inputs from a melanoma multidisciplinary team. Twelve patients with penile mucosal melanoma were analysed. Median [interquartile range (IQR)] age was 69.5 (67.25−81) years. The overall median follow-up (IQR) was 69.5 (20−114) months, while median follow-up for cancer-specific survival (CSS) was 11.5 (8−37) months. Location of the primary tumour was glans penis ( n  = 7), urethra ( n  = 2) and inner prepuce ( n  = 3). The CSS at 1, 2 and 5 years after primary surgery was 33%, 16.7% and 0%, respectively. The recurrence-free survival at 1, 3 and 5 months after the primary surgery was 90%, 67% and 56%, respectively. All patients with metastatic disease or with inguinal lymph node invasion at presentation, died within 25 months of the primary diagnosis. Management based on the modified EAU penile cancer guidelines still led to poor outcomes. We present a management diagram based on our experience. Abstract : Supplemental Digital Content is available in the text.